Estimation of antiparasitic activity of fungal extracts towards Leishmania donovani in murine model - Aseel Al-Musa; Muslim A.M. Altooma; Inaam M.N. Alrubayae (Romanian Journal of Infectious Diseases)
Background. Fungi produce many compounds have pharmaceutical usage. The current study was aimed to extract therapeutic compounds from fungi that grow in critical conditions and fungi that can be produced commercially which may have potential therapeutic activities against Leishmania donovani. The current study was aimed to extract therapeutic compounds from fungi that grow in critical conditions and fungi that can be produced commercially which may have potential therapeutic activities against Leishmania donovani. Methods. Two fungal isolates were used to evaluate antileishmanial activities of their extracts, the first due to Aspergillus terreus was isolated from salty sediments, while another represented local edible mushroom of Agaricus bisporus. The experiment was conducted in vivo after four weeks infection of Leishmania donovani. Infected mice were treated intraperitonially with 2 and 4 mg/kg daily for 10 days. Result. All compound has a significant effect on the viability and decrease the number of parasites in animal in comparison with pentostam, as well as, the M19 was appeared with highest effect in both concentrations. The method of examining infected tissues had a role in determining the number of parasites without affecting the percentage of presence in different treatments, as the numbers of parasites calculated in the tissue sections are more realistic than the number of parasites calculated in the printing method, as counting the parasite with tissue sections gives an impression of the spatial distribution of the parasite, whether within tissues or body fluids, unlike the printing method, which shows the presence of the parasite in body fluids and immune cells thus be suitable for the diagnosis of parasite amastigote in vivo. Conclusion. The compound extracted during study and diagnoses by GC-Mass technique are promising applicants for research on new drugs with anti-Leishmania activity derived from natural products.